Canine Lead Exposure in Automotive Repair Workshops: A Pilot Study Conducted in Cajamarca City, Peru. - Alcántara-Villar, G. (2025)
Introduction. Lead is a heavy metal widely used in the automotive industry and is considered one of the most harmful toxic agents for living organisms. Dogs inhabiting automotive repair workshops may experience chronic exposure to this metal, making them potential sentinels of environmental contamination. Objective. This study aimed to determine blood lead levels in dogs residing in automotive repair workshops in the city of Cajamarca (Peru). Materials and Methods. Blood lead levels were quantified in 16 dogs using graphite furnace atomic absorption spectrometry. Results and Discussion. Blood lead levels ranged from 0.427 μg/dL (0.0043 ppm) to 4.348 μg/dL (0.0435 ppm), with a mean ± standard deviation of 2.264 ± 1.243 μg/dL and a coefficient of variation of 54.907%. A proportion of the evaluated dogs (18.75%; 3/16) presented blood lead levels exceeding 3.5 μg/dL, the reference value established by the Centers for Disease Control and Prevention (CDC) for children in the United States, indicating environmental exposure within these settings. Conclusions. Although most dogs exhibited blood lead levels below the critical threshold for human health, the presence of elevated levels in certain individuals suggests potential long-term risks for both the animals and workshop personnel. These findings highlight the need for further research to identify sources of exposure and assess their implications within a One Health framework.